Understanding monsoon controls on the energy and mass balance of glaciers in the Central and Eastern Himalaya (Data Sets and Codes) - Stefan Fugger; Catriona Fyffe; Simone Fatichi; Evan Miles; Michael McCarthy; Thomas E. Shaw; Baohong Ding; Wei Yang; Patrick Wagnon; Walter Immerzee; Qiao Liu (Zenodo, 2022)
This repository contains AWS datasets for the modelling periods considered in the analysis presented in the research paper, together with ablation measurements, pre-processed forcing data, T&C model codes, outputs and scripts for analysing outputs. When previously published elsewhere, references and links to the full, original datasets are provided under References. Matlab scripts for executing the T&C model are provided and should work stand-alone on any machine with a Matlab version 2019b or later installed. Content to be complemented in an updated version of this repository.